A Progressive Report on Marxian Economic Theory: On the Controversies in Exploitation Theory since Okishio (1963) - Naoki Yoshihara (University of Massachusetts, Department of Economics, 2014)
This report explores the development of exploitation theory in mathematical Marxian economics by reviewing the main controversies surrounding the definition of exploitation since the contribution of Okishio (1963). The report first examines the robustness and economic implications of the debates on the Fundamental Marxian Theorem, developed mainly in the 1970s and 1980s, followed by the property relation theory of exploitation by Roemer (1982). Then, the more recent exploitation theory proposed by Vrousalis (2013) and Wright (2000) is introduced, before examining its economic implications using a simple economic model. Finally, the report introduces and comments on recent axiomatic studies of exploitation by focusing on the work of Veneziani and Yoshihara (2013a).
Keywords: D63; D51; 330; Fundamental Marxian Theorem; Property Relations Definition of Exploitation; Profit-Exploitation Correspondence Principle